Potensi Penggunaan Obat yang Tidak Tepat pada Peresepan Pasien Geriatri Rawat Jalan di RSD dr. Soebandi Jember Berdasarkan Beers Criteria (Potentially Inappropriate Medication Based on Beers Criteria in Geriatric Outpatients of dr. Soebandi District Hosp - Yeni Rahmawati Negara; Afifah Machlaurin; Ema Rachmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Inappropriate medication in geriatric is a serious problem because of its high morbidity, mortality, and healthcare costs. Beers Criteria 2012 is the compilation drugs that potentially inappropriate on geriatric patients. The objective of this study was to observe the percentage of inappropriate medication in geriatric outpatients prescription.This study used observational descriptive and retrospective design. The study showed that 69 patients (18.30%) from 377 patients prescribed with 92 inappropriate medication, 20 medication with strong and high quality evidence to be avoided based on Beers Criteria 2012. Amitriptyline was the most prescribed potentially inappropriate agents of 17 events. Keywords: geriatric, beers criteria,outpatients